2023
DOI: 10.1002/aah.10197
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of piscine francisellosis in Largemouth Bass from a public display exhibit in north‐central Florida, USA

Amanda Sheehy,
Khalid Shahin,
Alvin Camus
et al.

Abstract: ObjectiveThe Largemouth Bass Micropterus salmoides is an important freshwater fish that is native to the southeastern United States and is cultured for conservation, food, and for the sports fishing industry. Francisella orientalis is a globally distributed bacterial pathogen of warmwater fish species and is associated with granulomatous inflammation and high mortalities. Outbreaks of piscine francisellosis in the United States have been reported in only a few fish species. This study describes three case pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In this multi-year study (2018, 2019, 2020 and 2022), samples of cultured tilapia were analysed to detect fish pathogens using real-time PCR assays. Newly emerging or re-emergent bacterial fish diseases, such as francisellosis in the freshwater fish Micropterus salmoides (Sheehy et al, 2023) and the cichlid Herichthys cyanoguttatus (Chang et al, 2021), streptococcosis in tilapia (Cao et al, 2022;Zhang, 2021) and aeromoniasis in tilapia (Azzam-Sayuti et al, 2021) and spleens were the most frequent clinical signs, which were also observed in apparently healthy tilapias cultured in dams from Sinaloa state, located in north-western Mexico (Soto-Rodriguez et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In this multi-year study (2018, 2019, 2020 and 2022), samples of cultured tilapia were analysed to detect fish pathogens using real-time PCR assays. Newly emerging or re-emergent bacterial fish diseases, such as francisellosis in the freshwater fish Micropterus salmoides (Sheehy et al, 2023) and the cichlid Herichthys cyanoguttatus (Chang et al, 2021), streptococcosis in tilapia (Cao et al, 2022;Zhang, 2021) and aeromoniasis in tilapia (Azzam-Sayuti et al, 2021) and spleens were the most frequent clinical signs, which were also observed in apparently healthy tilapias cultured in dams from Sinaloa state, located in north-western Mexico (Soto-Rodriguez et al, 2013).…”
Section: Discussionmentioning
confidence: 95%